HLA-DQB1*03:01 strongly affects age of onset of type 1 narcolepsy independently of DQA1 and ethnicity - Lisan Zhang; Shuo Cai; Ashton Teng; Ling Lin; Fang Han; Han Yan; Seung-Chul Hong; Fabio Pizza; Giuseppe Plazzi; Luca Morandi; Ambra Stefani; Birgit Högl; et al. (Proceedings of the National Academy of Sciences, 2025)
Type 1 narcolepsy (T1N), an autoimmune disease associated with a disruption of hypocretin/orexin neurons, has conserved genetic effects transcending cultures and ethnicities. We pooled data from 5,339 cases from China, Europe, Korea, Japan, and the United States to conduct the first transethnic genome-wide association study (GWAS) on age of onset. Only one strong GWAS significant effect was observed across all ethnicities, summarized by the presence of human leukocyte antigen (HLA)-DQB1*03:01, and centered around the coding region of this gene. In contrast, HLA-DQB1*06:02-positive heterodimer (DQ0602) dosage did not strongly affect onset, and other known narcolepsy-associated genetic loci had minor effects. The HLA-DQB1*03:01 effect (mean −3.47 y, P = 1.7 × 10 −18 ) showed no heterogeneity across ethnic groups and was independent of common allelic variation at HLA-DQA1 in cis of HLA-DQB1*03:01 (DQA1*03:03; DQA1*05:05; DQA1*06:01). This effect may be due to a peptide being presented by all DQ0301 heterodimers (which are tolerant at the P1 binding position), or it may stem from genetic effects of HLA on T cell receptor genes TCRA and TCRB usage that influence the TCR repertoire. Using bulk and single-cell RNA sequencing data across Chinese and Caucasians, who have distinct patterns of linkage disequilibrium around DQB1*03:01, we found that HLA-DQB1*03:01 alters TCR repertoire at specific positions, most significantly within the CDR2α, CDR2β, and CDR3β loops. These results illustrate the remarkable conservation of genetic effects in narcolepsy across ethnicity. The identification of the disease-causing T cells will be crucial for elucidating how this finding relates to the underlying pathophysiology.